How will the digital twin shape the future of industry 5.0? - Barata, João; Kayser, Ina (Technovation, 2024)
Industry 5.0 is on the horizon, but the role of digital twins (DTs) as one of its major technological enablers is far from being understood. This article begins with a bibliometric analysis and a systematic review, followed by a discussion of insights obtained from the literature through the lens of strong structuration theory. The results include a description of the new paradigm of future-oriented and responsible physical-digital convergence, a research agenda, and the proposal of the structure – agency (SA)–DT framework to guide advances in Industry 5.0 with digital twins. A concept-centric analysis is used to identify use cases, impacts, redesigned forms of physical–digital interaction, challenges, and the changes in both human and non-human agents increasingly intertwined in more advanced DT solutions. Moreover, this study reveals how digital twins can be deployed to address, in an integrated manner, the three main pillars of Industry 5.0: human-centric, sustainable, and resilient industry transformation. Practitioners may find our contribution helpful for their Industry 5.0 roadmaps, which require more ample interaction with society at all levels and evidence of responsible practices for current and future generations. [Display omitted] •Industry 5.0 calls for a human-centric, resilient, and sustainable transformation.•Digital twins are one of the most promising technological enablers of Industry 5.0•This paper describes the new paradigm of future-oriented and responsible physical-digital convergence in industry.•The Structure – Agency (SA)– Digital Twin (DT) framework is proposed to guide advances in Industry 5.0